2011
DOI: 10.1111/j.1467-3010.2011.01889.x
|View full text |Cite
|
Sign up to set email alerts
|

Diets of minority ethnic groups in the UK: influence on chronic disease risk and implications for prevention

Abstract: Summary Introduction Definitions of ethnic groups and demographics of minority ethnic groups in the UK Overview of the health profile and dietary habits of minority ethnic groups in the UK Factors affecting food choice Traditional diets of minority ethnic groups Nutritional interventions and health promotion among minority ethnic groups Conclusion Acknowledgements References Summary According to the latest census, non‐white minority ethnic groups made up 7.9% of the UK's population in 2001. The largest of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 66 publications
4
89
0
1
Order By: Relevance
“…The dietary habits of minority ethnic groups are affected by a wide variety of factors including income, socio-economic status, religious beliefs, food availability and food beliefs [46]. Whilst appreciating potential resistance to change, independently of ethnicity this African/Caribbean pattern was associated with increased risk of GDM and it remains a potential target for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary habits of minority ethnic groups are affected by a wide variety of factors including income, socio-economic status, religious beliefs, food availability and food beliefs [46]. Whilst appreciating potential resistance to change, independently of ethnicity this African/Caribbean pattern was associated with increased risk of GDM and it remains a potential target for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, supplementation of u-3 PUFAs (fish oil) did not improve insulin sensitivity in South Asians (69,76). Moreover, other studies even reported that South Asian diets are healthier compared with White Caucasian diets (lower intake of fat) (73,77,78,79). Furthermore, different regional and religious South Asian communities in the UK had a similar, markedly higher prevalence of diabetes compared with white Europeans, despite the known dietary, cultural, and socioeconomic differences between these different South Asian communities.…”
Section: Diet and Exercisementioning
confidence: 99%
“…… [Over the course of multiple visits] my interest to get some knowledge will go away." (Man, group 8) negative effect on populations who may already have difficulty accessing care (e.g., immigrants, older people), and our participants clearly identified this barrier as a priority for intervention. Moreover, the role of physicians in the South Asian population is culturally significant, and the population places high value on the "physician directive" (confirmed by A.G.).…”
Section: Box 1: Summary Of Main Findingsmentioning
confidence: 99%